An assessment and analytical report for integrated agriculture-aquaculture (IAA) systems in Egypt - Sadek, Sherif; Elewa, Ahmed; Ahmed, Nour; Munir, Salma; Mahfouz, Abdel-Rahman; Nasr-Allah, Ahmed (WorldFish, 2023)
The study concludes that successful development of innovative IAA and sustainable scaling in Egypt require creating innovative solutions to implement these systems. During the next 10 years, IAA will become an important approach for sustainable development. Recommended innovations include the following: • Help stakeholders use information communication technology (ICT), smart sensing and the internet of things (IOT) for optimal use of resources. • Adopt hybrid water management in the fish farm component of IAA by using both the flow-through system, partial recirculating aquaculture system (PRAS) and the recirculating aquaculture system (RAS) based on the requirements for crop irrigation. • Support product network marketing and establish IAA pilot farms as demonstration farms for private farmers so that they can learn how to manage IAA systems. • Help farmers learn how to adopt new techniques through applied research, training, interactions and shared knowledge.